Is type 2 diabetes mellitus a predictive factor for incontinence after laparoscopic radical prostatectomy?: A matched pair and multivariate analysis - Teber, Dogu; Sofikerim, Mustafa; Ates, Mutlu; Gözen, Ali Serdar; Güven, Oguz; Sanli, Öner; Rassweiler, Jens (The journal of urology, 2010)
Purpose: - - We evaluated the effect of diabetes mellitus on incontinence after laparoscopic radical prostatectomy. - - Materials and Methods: - - From a series of 2,071 patients 135 with type 2 diabetes mellitus undergoing laparoscopic radical prostatectomy without radiotherapy and with a minimum followup of 24 months were identified. These patients were randomly matched with 135 nondiabetic controls for age, body mass index, preoperative prostate specific antigen, clinical stage, neoadjuvant hormonal therapy, prostate volume, previous surgery, surgeon skills, surgical approach, presence of bladder neck sparing, lymphadenectomy, technique of urethrovesical anastomosis and attempted nerve sparing surgery. - - Results: - - Using multivariate analysis age, diabetes mellitus and duration of diabetes mellitus were independent factors for post-prostatectomy incontinence in the whole group. Early continence (0 to 3 months) was observed in 43.7% of patients with diabetes and in 57.8% of nondiabetic controls which was statistically significant (p = 0.02). The rates of continence in patients with diabetes mellitus for 5 or more years at 3, 12 and 24-month evaluations were less than those in patients with diabetes mellitus for less than 5 years, and the difference was statistically significant (36% vs 50%, p = 0.001; 63.9% vs 82.4%, p = 0.02; 91.8% vs 98.6%, p = 0.03, respectively). - - Conclusions: - - Patients with type 2 diabetes mellitus need longer to recover continence than nondiabetics after laparoscopic radical prostatectomy. However, type II diabetes mellitus did not affect overall return to continence. Patients with diabetes mellitus for 5 or more years have an almost 5 times increased risk of post-prostatectomy incontinence compared to those with diabetes mellitus for less than 5 years. Diabetic patients should be counseled for the potential negative impact of diabetes mellitus on the recovery of continence after laparoscopic radical prostatectomy.
Gesehen am 26.10.2023